IκBNS induces Muc5ac expression in epithelial cells and causes airway hyper‐responsiveness in murine asthma models. Issue 7 (23rd November 2016) - Yokota, M.; Tamachi, T.; Yokoyama, Y.; Maezawa, Y.; Takatori, H.; Suto, A.; Suzuki, K.; Hirose, K.; Takeda, K.; Nakajima, H.
Abstract: Background: In allergic asthma, environmental allergens including house dust mite (HDM) trigger pattern recognition receptors and activate downstream signaling pathways including NF‐κB pathways not only in immune cells but also in airway epithelial cells. Recent studies have shown that NF‐κB activation is regulated positively or negatively depending on the cellular context by IκBNS (encoded by the gene Nfkbid ), one of atypical IκB proteins, in the nucleus. Therefore, we hypothesized that IκBNS expressed in immune cells or epithelial cells is involved in the regulation of asthmatic responses. Aim: To determine the roles of IκBNS in HDM‐induced asthmatic responses. Methods: Roles of IκBNS in HDM‐induced airway inflammation and airway hyper‐responsiveness (AHR) were examined by using IκBNS‐deficient ( Nfkbid −/− ) mice. Roles of IκBNS expressed in hematopoietic cells and nonhematopoietic cells were separately evaluated by bone marrow chimeric mice. Roles of IκBNS expressed in murine tracheal epithelial cells (mTECs) were examined by air–liquid interface culture. Results: House dust mite‐induced airway inflammation and AHR were exacerbated in mice lacking IκBNS in hematopoietic cells. In contrast, HDM‐induced airway inflammation was exacerbated, but AHR was attenuated in mice lacking IκBNS in nonhematopoietic cells. The induction of Muc5ac, a representative mucin in asthmatic airways, was reduced in Nfkbid −/− mTEC, whereas the induction of Spdef, a master regulator of goblet cell metaplasia, was not impaired in Nfkbid −/− mTEC. Moreover, IκBNS bound to and activated the MUC5AC distal promoter in epithelial cells. Conclusion: IκBNS is involved in inducing Muc5ac expression in lung epithelial cells and causing AHR in HDM‐induced asthma models.